ID 286 – Auditory oddball event-related potentials cortical sources are related to cerebrospinal fluid (CSF)® amyloid (A®) level in amnesic MCI subjects. Issue 3 (March 2016) - Cordone, S.; Del Percio, C.; Marzano, N.; Noce, G.; Bagnoli, C.; Rossini, P.M.; Soricelli, A.; Famá, F.; Bartres Faz, D.; Blin, O.; Payoux, P.; Bordet, R.; et al.
Abstract : Aim: In the framework of IMI PharmaCog project (Grant Agreement no. 115009), this study evaluated whether cortical sources of AO-ERPs are related to cerebrospinal fluid (CSF)® amyloid (A®) level in amnesic Mild Cognitive Impairment (MCI) subjects. Methods: Artifact-free AO-ERPs (19 electrodes) were recorded in 115 MCI subjects. Individual datasets were divided into those with high CSF A® level (61 A®-negative, CSF A® > 550 pg/ml) and those with low CSF A® level (43 A®-positive, CSF A® < 550 pg/ml). Cortical sources of late positive frontal (P3a; novelty of rare targets) and posterior (P3b; attention and reaction to rare targets) peak components of AO-ERPs were estimated by sLORETA package. sLORETA T -test compared these sources between the two MCI groups ( p  < 0.05, corrected). Results: The ANOVA for the P3a peak illustrate a statistically significant interaction effect ( F  = 2.87; p  = 0.006) between the factors Group and Brodmann Area (BA 10 and 11). The ANOVA for the P3b peak illustrate a statistically significant interaction effect ( F  = 2.745; p  = 0.008) between the factors Group and BA (BA 5, 7, 23, 31). Conclusions: The present study provides support to the hypothesis that specific neurophysiological markers may enrich the discrimination of aMCI subjects in an early stage of prodromal Alzheimer's disease (AD) for early diagnosis and preventive treatments.